(untitled) (Regional aspects of productive forces development of Ukraine, 2019)
The article reveals the peculiarities of the formation of the image of a modern educational institution, in particular, its definitions and components, the essence of formation and monitoring, and the necessity of the introduction of image management in the marketing system of the modern university are presented. Perspectives of application of innovative technologies in formation of the brand of the employer, construction of an effective marketing strategy and behavior in the labor market are considered.